2013
DOI: 10.1186/1742-2094-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 affects migration of hippocampal neural progenitors following status epilepticus in rats

Abstract: BackgroundEpilepsy is a common brain disorder characterized by a chronic predisposition to generate spontaneous seizures. The mechanisms for epilepsy formation remain unknown. A growing body of evidence suggests the involvement of inflammatory processes in epileptogenesis. In the present study, we investigated the involvement of monocyte chemoattractant protein-1 (MCP-1) in aberrant migration of hippocampal progenitors in rats after the insult of status epilepticus (SE).MethodsSE was induced with pilocarpine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
20
1
Order By: Relevance
“…In rodent models of temporal lobe epilepsy, seizures have been shown to transiently increase CCL2 and CCR2 expression in the hippocampus. In dentate gyrus and CA1/CA3 pyramidal layers, CCL2 upregulation after seizures has been detected in both neurons and glial cells, whereas CCR2 induction has been observed in astrocytes, microglia, and ectopic progenitors of hilar neurons (Manley et al, 2007;Foresti et al, 2009;Hung et al, 2013;Arisi, 2014;Arisi et al, 2015;Cerri et al, 2016) (Fig. 1B).…”
Section: Expression Of Ccl2 and Its Receptor In The Epileptic Brainmentioning
confidence: 88%
See 1 more Smart Citation
“…In rodent models of temporal lobe epilepsy, seizures have been shown to transiently increase CCL2 and CCR2 expression in the hippocampus. In dentate gyrus and CA1/CA3 pyramidal layers, CCL2 upregulation after seizures has been detected in both neurons and glial cells, whereas CCR2 induction has been observed in astrocytes, microglia, and ectopic progenitors of hilar neurons (Manley et al, 2007;Foresti et al, 2009;Hung et al, 2013;Arisi, 2014;Arisi et al, 2015;Cerri et al, 2016) (Fig. 1B).…”
Section: Expression Of Ccl2 and Its Receptor In The Epileptic Brainmentioning
confidence: 88%
“…Since IL-1b is mainly produced and released by activated microglia in the epileptic brain (Vezzani et al, 1999), it is likely that CCL2 increases seizures through IL-1b. Finally, CCL2 might also be involved in neuropathological changes that accompany seizures, such as ectopic migration of neuronal progenitors in the dentate gyrus (Hung et al, 2013). Thus, CCL2/CCR2 signaling may act as a key proinflammatory factor in the epileptic brain by both directly increasing neuronal excitability and inducing downstream inflammatory effectors.…”
Section: Open Questionsmentioning
confidence: 98%
“…Signaling through CXCR2 has been shown to increase neuronal excitability, potentially through the association of CXCR2 with GluR1 AMPA receptors (Lax et al 2002; Wang et al 2008). CCl2, CCL4 and CCR7 are elevated in brain tissue from epilepsy patients, as well as in animal models (Fabene et al 2010; Lehtimaki et al 2003; Liimatainen et al 2013; Vezzani et al 2008; Vezzani et al 2002; Hung et al 2013). In concordance with this, we found the Ccl2 and Ccr7 genes to feature a prolonged upregulation following PIC challenge (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, we recently reported that CCR2 deficiency, through genetic manipulation in mice, was sufficient to prevent the aberrant migration of new neurons observed in vivo following irradiation (Belarbi et al, 2013). Similarly, in the pilocarpine-induced status epilepticus rat model, the blockade of the MCP-1/CCR2 interaction with a selective CCR2 antagonist attenuated the ectopic migration of neuronal progenitors into the hilus (Hung et al, 2013). Collectively, these findings indicate that adult-born neurons have the capacity to migrate to the site of damage in response to the chemokine MCP-1/CCR2 signaling pathway.…”
Section: Distribution Of Adult-born Neurons In the Inflamed Hippocampusmentioning
confidence: 99%